(untitled) (LACCEI, 2024)
Ceramic manufacturing plants base their operations around continuous and automated production, prioritizing the proper maintenance of machines to avoid production losses. In this sense, this research focuses on reducing defective products since it generates the greatest economic loss in the case study. For this purpose, a production management model based on TPM and SMED tools is proposed, contributing to the increase of availability and reduction of the mean time between machinery failures. Finally, the results are validated based on the line production, which represents 33.55% of the monetary value. Finally, the proposed model manages to decrease the set-up time and increase the availability of machinery to 32.31% and 88.4%, respectively, obtaining as a critical result the reduction of defective products from 5.44% to 2.33%, allowing access to a high level of competition in its sector and a decrease in operating cost overruns.